Factors influencing tax avoidance activity: an empirical study from Indonesia stock exchange - Jingga, Vinny; Lina, Lina (OMJP Alpha Publishing, 2017)
This research aims to examine the influence of the firm characteristics to tax avoidance activity in the listed companies in Indonesia. This research uses the proxies of firm size, leverage, capital intensity, inventory intensity as the firm characteristics and return on asset and market-to-book ratio as control variables. The samples of this research consist of 158 firm-year observations from all industries which are listed in Indonesia Stock Exchange during 2010-2013. The samples are selected by using purposive sampling method through several specific sample criteria. The technique used to examine hypothesis is multiple regression analysis. The result of this research reveals that leverage has a positive influence towards tax avoidance activity, while the rest variables have no influence towards tax avoidance activity.